USING ‘THE DART METHOD’ TO IMPROVE SENIOR HIGH SCHOOL STUDENTS’ READING COMPREHENSION OF A NARRATIVE TEXT - Tyara Wulandari; Yetti Zainil (Universitas Negeri Padang, 2018)
Reading as one of English skills should be taught to the students. However, students still find some difficulties in reading due to some factors: lack of background knowledge, motivation, and vocabulary. Therefore, teacher should select an appropriate method to solve those problems. This paper is aimed to inform how to use a teaching method which is called Directed Activities Related to the Text (DART) method in teaching reading narrative text to senior high school students. DART method relies on group discussion to achieve learning objectives. There are some purposes in this method: to help the students to comprehend the information in the text, to enrich students’ vocabulary, and to improve students’ interest in reading since the students involved actively in learning activities. Teaching reading comprehension thorough this method of a narrative text consists of two stages: the first stage, reconstruction activity, requires students to reconstruct the text through predicting, completing, and sequencing the text. While the second stage, analysis activity, requires students explore the text by analyze the elements of the text thorough questioning, highlighting, segmenting and labeling, and diagram constructing. Therefore, thorough these activities the students can understand and comprehend the text easily.